2022
DOI: 10.3389/frph.2022.782915
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infections and Male Infertility: A Comprehensive Review of the Role of Oxidative Stress

Abstract: Viral infections have been a part of human existence to date, though viruses have posed a huge threat with various outbreaks lately. These threats are associated with reproductive health challenges, especially male infertility. The prime focus of this review is to highlight the mechanisms associated with viral infection-induced male infertility/subfertility and identify new treatment strategies with the aim to preserve male fertility. The reviewed data showed that viral infections stimulate inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 192 publications
0
6
0
Order By: Relevance
“…Systemic viral infection negatively impacts sperm production and the quality of semen [58]. Further, such viral infections may induce damage to sperm DNA, impairing their ability to fertilize oocytes [59,60]. Based on our current analysis in this area, very few studies (n = 3) reported seminal oxidative stress and damage to sperm DNA induced by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 92%
“…Systemic viral infection negatively impacts sperm production and the quality of semen [58]. Further, such viral infections may induce damage to sperm DNA, impairing their ability to fertilize oocytes [59,60]. Based on our current analysis in this area, very few studies (n = 3) reported seminal oxidative stress and damage to sperm DNA induced by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 92%
“…This has been associated with the global decline in sperm quality ( 4 , 5 ), which occurs in concert with hormonal disruption ( 4 ). Testicular pathologies (such as cryptorchidism, testicular torsion and testicular cancer) ( 6 8 ), lifestyle factors, such as diets, smoking, energy dyshomeostasis and metabolic disorders ( 9 – 11 ), viral infections ( 12 , 13 ), pharmaceuticals ( 14 ), and environmental toxicants, such as plasticizers and pesticides ( 15 , 16 ) have been implicated in the pathogenesis of hormonal disruption and decline in sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using public single-cell RNA sequencing datasets reported a high expression level of ACE2 and TMPRSS2 in the testis including the spermatogonia, peritubular myoid cells, testis somatic cells, and spermatogonial stem cells [ 19 ], but similar studies did not find ACE2/TMPRSS2 co-expression in any type of testicular tissue [ 20 ], suggesting that testicular cells do not have a high risk of viral entry and infection and that the impaired testicular function could occur through indirect mechanisms, such as high fever and inflammation promoted by the cytokine storm. Furthermore, some studies showed that SARS-CoV-2, similar to other viruses including HIN1, Zika, HIV, hepatitis, and papilloma, could alter testicular function by promoting an oxido-inflammatory response, atrophy of the seminiferous tubules and Sertoli cells, and reduced Leydig cell mass with hypotestosteronemia [ 21 ]. In addition, several studies have demonstrated that some viruses can be sexually transmitted because they evade the host immune response via extracellular vehicles (EVs).…”
Section: Introductionmentioning
confidence: 99%